Estudo para a implementação de uma planta de produção de amido de milho - Geraldi, Claudinéia Aparecida Queli (2010)
In this work was developed a new layout processing for the production of com starch and byproducts as compared to the traditional process. This development was motivated by the diversity of productive arrangements for the production of com starch found in the literature and industry. The layout took into account the peculiarities of the Brazilian market and introduced technological innovation by the use of equipment traditionally used in cassava starch manufacturers, for the production of com starch, and by changes in the process of maceration. The new layout was implemented in an industrial unit in the West region of Parana. Was performed the physical-chemical analysis of the grains of hybrid com, slightly e toothed, 2007/2008 crop produced in western of Parana state, and as germ bran (produced through dry degermination process), starch and bran of gluten 60 and gluten 21 obtained by wet milling of degerminated com. The properties analyzed were percentage of moisture, starch content, ether extract, total protein, ash, fiber, pH, granulometry, foreign bodies, impurity, rot and sprouted, grains damaged. Although this study was developed a methodology capable to estimate the costs and investments involved in a production process of com starch and byproducts. The methodology used a cost estimate based on national equipment and correlations proposed by PERLINGEIRO (2005), allowing evaluation, quickly and accurately, different configurations of equipment during the design stage of the process, thus determining the final cost of kilogram of corn starch. By comparing the values of kilogram of starch produced with the market price and with cassava starch price, were observed that the starch simulated in this study presented values extremely competitive.